1990
DOI: 10.1002/gcc.2870020106
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical, molecular, and cytogenetic analysis of a consecutive series of 20 peripheral t‐cell lymphomas and lymphomas of uncertain lineage, including 12 Ki‐I positive lymphomas

Abstract: Although several independent series of non-Hodgkin's lymphomas (NHLs) have been subjected to cytogenetic studies or analyses of lineages by assaying for clonal immunophenotypes and clonal rearrangements affecting immunoglobulin (IG) and T-cell receptor (TCR) genes, no published reports exist of series of non-B-cell NHLs on which cytogenetic, immunohistochemical, and IG and TCR gene rearrangement studies have been undertaken together. Among 343 NHLs ascertained prospectively between January 1984 and December 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…In addition to t( 14; 18), t( 11; 14), and t(8; 14) and variants, two other specific translocations, t(3;22) and t(2;S) have been observed with significant frequency and have been linked to histologic subtypes of N H L Kaneko et al, 1989;Le Beau et al, 1989, Offit et al, 1989bEbrahim et al, 1990;Leroux et al, 1990). These studies have identified additional structural and numerical chromosome aberrations that often accompany the specific translocations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to t( 14; 18), t( 11; 14), and t(8; 14) and variants, two other specific translocations, t(3;22) and t(2;S) have been observed with significant frequency and have been linked to histologic subtypes of N H L Kaneko et al, 1989;Le Beau et al, 1989, Offit et al, 1989bEbrahim et al, 1990;Leroux et al, 1990). These studies have identified additional structural and numerical chromosome aberrations that often accompany the specific translocations.…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy material was divided for histopathology, cytogenetic analysis, cell surface marker analysis, and gene rearrangement studies as previously described (Ebrahim et al, 1990). A subset of nine cases of mycosis fungoides were excluded from this analysis.…”
Section: Materials a N D Methods Tissue Evaluationmentioning
confidence: 99%
“…4 The status of ALCL as a discrete entity had long been controversial, 5,6 and its recent separation into at least two subsets (see Discussion) stems from cytogenetic and molecular studies of the translocation seen in about 40 to 60% of cases, t(2;5)(p23;q35). [7][8][9] In 1994, the t(2;5) was found to involve a novel gene at 2p23 encoding a tyrosine kinase, ALK (anaplastic lymphoma kinase), and the NPM (nucleophosmin) gene at …”
mentioning
confidence: 99%
“…38 Its molecular structure, namely the genes involved by the breakpoints, has recently been characterized, allowing detection of the translocation by the polymerase chain reaction. A recurrent translocation, t(2;5)(p23;q35), has recently been described in Ki-1 ALCL.…”
Section: Discussionmentioning
confidence: 99%